Clinical characteristics, risk factors and outcome of critically ill immunocompromised patients with bloodstream infections and sepsis - Nirusdee Vonineng; Yuda Sutherasan; Jackrapong Bruminhent (PLoS ONE, 2025)
Background Immunocompromised patients with sepsis face higher mortality than immunocompetent individuals. However, data on bloodstream infections (BSIs) and sepsis among critically ill immunocompromised (CII) patients remain limited. We aimed to describe the epidemiology, outcomes, and mortality risk factors of BSIs in this population. Methods We conducted a retrospective cohort study of CII patients admitted to the medical ICU between January 2022 and December 2023 with suspected sepsis or septic shock. Patients with BSIs confirmed by positive blood cultures were identified. Propensity score matching (1:1) without replacement was used to create comparable groups for Cox regression analysis of 30-day all-cause mortality. Results Among 211 CII patients (mean age (SD) 61 (16) years, 57% male), 85 (40.3%) had BSIs. The median SOFA and APACHE II scores were 7 (IQR 4–11) and 16 (IQR 14–20), respectively. Immunosuppression was due to hematologic malignancy (37.4%), solid tumors (27.0%), autoimmune diseases (19.0%), solid organ transplantation (5.7%), and other causes (10.4%). Gram-negative rods predominated (65.9%), notably P. aeruginosa (17%), E. coli (17%), and K. pneumoniae (14%). The overall 30-day mortality rate was 48.8%. In the matched cohort (n = 170), higher SOFA scores [HR 1.12; 95% CI, 1.04–1.20; p = 0.003] and lactate >4 mmol/L [HR 1.91; 95% CI, 1.06–3.42; p = 0.031] were associated with increased mortality. Underlying COPD/asthma was associated with lower mortality [HR 0.20; 95% CI, 0.06–0.66; p = 0.009]. Conclusion BSIs are frequent in CII patients and linked to high mortality. Severity of illness and hyperlactatemia predict poor outcomes, while preexisting pulmonary disease may offer a survival benefit.